2021
DOI: 10.3390/dj9060059
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma Improves Shear Bond Strength of Veneering Composite to Zirconia

Abstract: Chipping of veneering is the most common clinical complication for zirconia restorations. Veneering composite could be a promising alternative to renew restorations. Zirconia discs (3-YSZ) were prepared with varying surface treatments and bonded to indirect composite as follows: air abrasion and Scotchbond Universal (A/SU); air abrasion and Clearfil Ceramic Primer (A/C); air abrasion and MKZ Primer (A/M); air abrasion and Monobond Plus (A/MP); silica-coating and Scotchbond Universal (S/SU); air abrasion (AP/SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Other surface treatments for PEEK that resulted in comparable or higher bond strength values included the use of cold atmospheric plasma and an erbium-doped yttrium aluminum garnet laser. 14,21 These methods were not available for the present study, and because the bond strength reported in those studies were in a range similar to that of alumina airborne-particle abrasion, the PEEK specimens and Ti-bases were pretreated by using alumina airborne-particle abrasion for standardization. Airborne-particle abrasion has been recommended for both bonding on PEEK and bonding on Ti-bases to obtain surfaces with improved adhesive properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other surface treatments for PEEK that resulted in comparable or higher bond strength values included the use of cold atmospheric plasma and an erbium-doped yttrium aluminum garnet laser. 14,21 These methods were not available for the present study, and because the bond strength reported in those studies were in a range similar to that of alumina airborne-particle abrasion, the PEEK specimens and Ti-bases were pretreated by using alumina airborne-particle abrasion for standardization. Airborne-particle abrasion has been recommended for both bonding on PEEK and bonding on Ti-bases to obtain surfaces with improved adhesive properties.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, the primers and resin cements used in the present study to bond the PEEK specimens to Ti-bases have been reported to provide durable bond strength values, even after artificial aging. 14 With regard to the adhesive systems for Ti-bases, one of the most widely used adhesive systems (Monobond Plus) and the adhesive system recommended by the PEEK manufacturer (MKZ primer) were used. 11,21 However, the authors are unaware of studies using either DTK adhesive or Multilink hybrid abutment to bond PEEK to Ti-bases, suggesting the lack of knowledge on bonding of PEEK on Ti-bases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been investigated for its potential application in the preparation and treatment of cavities, composite restorations, root canal disinfection, functionalization of dental implant surfaces, disinfection, decontamination, and sterilization of dental instruments. [8][9][10][11][12][13] CAP has emerged as a prospective dental treatment option [14] due to its noninvasive nature, lack of chemical residue, and vibration. [4,15] It is now possible to apply CAP to heat-sensitive biological materials, such as tissue, thanks to recent developments in devices that produce CAP.…”
Section: Introductionmentioning
confidence: 99%
“…CAP has emerged as a prospective dental treatment option [ 14 ] due to its noninvasive nature, lack of chemical residue, and vibration. [ 4,15 ] It is now possible to apply CAP to heat‐sensitive biological materials, such as tissue, thanks to recent developments in devices that produce CAP.…”
Section: Introductionmentioning
confidence: 99%